Engagement and disengagement at work : drivers and organizational practices to sustain employee passion and performance - Imperatori, Barbara (Springer, 2017)
*Hotline check pending. At MS submission* This book offers a concise summary of cutting-edge research and practical implications about employee engagement. The author presents a clear perspective on the meaning of employee engagement, its antecedents and consequences are presented with evidences. Based on latest research results, the book discusses organizational practices which enhance people engagement focusing on the new trends of the HRM domain such as well-being practices, e-HRM systems and social volunteering initiatives. The detailed analysis also takes the recent complaints about the HR function into account. This book emphasizes that modern organizations require passionate people to thriving in a rapidly changing world, and it is important to understand why, despite the growing relevance of employee engagement, disengaged persists.
Keywords: Employee motivation.; Organizational behavior.; Psychology, Industrial.; elektronické knihy; electronic books